Mechanism of All-trans-retinal Toxicity with Implications for Stargardt Disease and Age-related Macular Degeneration - Chen, Yu (American Society for Biochemistry and Molecular Biology, 2012)
Compromised clearance of all-trans-retinal (atRAL), a component of the retinoid cycle, increases the susceptibility of mouse retina to acute light-induced photoreceptor degeneration. Abca4(−/−)Rdh8(−/−) mice featuring defective atRAL clearance were used to examine the one or more underlying molecular mechanisms, because exposure to intense light causes severe photoreceptor degeneration in these animals. Here we report that bright light exposure of Abca4(−/−)Rdh8(−/−) mice increased atRAL levels in the retina that induced rapid NADPH oxidase-mediated overproduction of intracellular reactive oxygen species (ROS). Moreover, such ROS generation was inhibited by blocking phospholipase C and inositol 1,4,5-trisphosphate-induced Ca(2+) release, indicating that activation occurs upstream of NADPH oxidase-mediated ROS generation. Because multiple upstream G protein-coupled receptors can activate phospholipase C, we then tested the effects of antagonists of serotonin 2A (5-HT(2A)R) and M(3)-muscarinic (M(3)R) receptors and found they both protected Abca4(−/−)Rdh8(−/−) mouse retinas from light-induced degeneration. Thus, a cascade of signaling events appears to mediate the toxicity of atRAL in light-induced photoreceptor degeneration of Abca4(−/−)Rdh8(−/−) mice. A similar mechanism may be operative in human Stargardt disease and age-related macular degeneration.